Efficacy of plastic shopping bag tax as a governance tool: lessons for South Africa from Irish and Danish success stories - Muposhi, Asphat; Mpinganjira, Mercy; Wait, Marius (AOSIS, 2022)
Orientation: The negative environmental effects of single-use plastic shopping bags have prompted national governments to implement interventions to curtail their use. Plastic bag tax is gaining prominence as a single-use plastic shopping bag governance tool in several jurisdictions.